Exploring the Relationship Between Residential Perceptions and Satisfaction: A Demographic Analysis in Wuhan, China - Mengyao Hong; Hongrui Li; Wei Wei; Jialing Chao; Junnan Xia (Land)
Previous research has shown that residents’ perceptions significantly influence their residential satisfaction. However, the internal relationships within these perceptions and their impact on satisfaction across different demographic groups remain underexplored. This study, guided by Maslow’s hierarchy and Homo-urbanicus, categorizes residents’ perceptions into four dimensions: safety, convenience, comfort, and aesthetics. Using multi-group structural equation modeling, an empirical investigation was conducted in Wuhan, China. The findings indicate that perceptions of safety, convenience, comfort, and aesthetics exert a chained mediating effect on satisfaction, with the impact pathway being safety → convenience → comfort → aesthetics → satisfaction. Both convenience and comfort also directly influence satisfaction. Notably, perception pathways vary among different demographic groups: women are more influenced by perceptions, younger individuals prioritize convenience and aesthetics, and older adults emphasize safety and comfort. This study highlights demographic differences in perception and satisfaction levels, offering insights into the hierarchical relationships among resident perceptions and their impact pathways on satisfaction. This research suggests enhancing residential satisfaction by optimizing these perceptions, particularly for vulnerable groups. Policy implications include improving human settlement elements at the residential area level, incorporating cultural and innovative elements, and expanding public participation in communities.